2022
DOI: 10.3390/ma15041462
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Computer-Assisted Flapless Implant Placement by Means of Mucosa-Supported Templates in Complete-Arch Restorations: A Systematic Review

Abstract: The aim of this study was to systematically review the current scientific literature regarding the accuracy of fully guided flapless implant positioning for complete-arch rehabilitations in edentulous patients and to assess if there was any statistically significant correlation between linear deviation at shoulder point, at apex point and angular deviation. The electronic and manual literature search of clinical studies was carried out using specified indexing terms. A total of 13 studies were eligible for qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Some authors have suggested that CAIS could reduce intraoperative complications by helping the surgeon avoid damaging sensitive anatomic structures such as the mandibular nerve and the sinus, as well as avoid proximity to roots of neighboring teeth 4 . Some have suggested CAIS could reduce the invasiveness, complexity, and duration of surgical interventions, while others have reported increasing patients’ satisfaction and acceptance 5 . Finally, as this technology aims to empower the proper prosthetic‐driven implant placement, it could potentially impact the long‐term outcomes of implant therapy by allowing implant placement in the optimal position and angulation for prosthetic designs that could promote sustainable esthetic outcomes and health of the peri‐implant tissue 6,7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have suggested that CAIS could reduce intraoperative complications by helping the surgeon avoid damaging sensitive anatomic structures such as the mandibular nerve and the sinus, as well as avoid proximity to roots of neighboring teeth 4 . Some have suggested CAIS could reduce the invasiveness, complexity, and duration of surgical interventions, while others have reported increasing patients’ satisfaction and acceptance 5 . Finally, as this technology aims to empower the proper prosthetic‐driven implant placement, it could potentially impact the long‐term outcomes of implant therapy by allowing implant placement in the optimal position and angulation for prosthetic designs that could promote sustainable esthetic outcomes and health of the peri‐implant tissue 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“… 4 Some have suggested CAIS could reduce the invasiveness, complexity, and duration of surgical interventions, while others have reported increasing patients’ satisfaction and acceptance. 5 Finally, as this technology aims to empower the proper prosthetic‐driven implant placement, it could potentially impact the long‐term outcomes of implant therapy by allowing implant placement in the optimal position and angulation for prosthetic designs that could promote sustainable esthetic outcomes and health of the peri‐implant tissue. 6 , 7 Optimal positioning of the implants may also reduce the cost of reconstruction, by allowing the use of stock abutments and minimizing the need for expensive customized solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Digital-implant-assisted surgery has been largely developed in the last years, including different systems such as static and dynamic computer-assisted implant placement. Static-system implant placement has been widely used from single tooth replacement to complete arch rehabilitation, providing good clinical results in terms of invasiveness and accuracy [ 6 ]. The use of a static printed template is synonymous of pre-planned implant coordinates without the possibility of visual control of the implant recipient site while the drills are in function in combination with a dedicated surgical kit with an appropriate drill set.…”
Section: Discussionmentioning
confidence: 99%
“…The rehabilitation of partially or completely edentulous jaws with dental implants is a preferred treatment approach these days [ 1 , 2 , 3 , 4 ]. Different surgical and prosthetic protocols have been proposed to optimize both implant success and patient satisfaction [ 5 , 6 , 7 ]. Among them, immediate implant placement and immediate provisionalization were favorably preferred by patients and clinicians because of the reduced treatment time [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anchor pins or screws are most commonly used to fix templates. 10 However, this method has the following critical limitations. First, it is much more difficult to secure stability than to obtain adequate support from hard tissue.…”
Section: Case Reportmentioning
confidence: 99%